CAMPUR KODE PADA PODCAST THE CATCH UP CLUB DI YOUTUBE - Sutiara Mayulis; Felisya Wanna Putri; Fatmawati Fatmawati (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This research is motivated by the phenomenon of code-mixing as a growing sociolinguistic trend in digital media, particularly YouTube and podcasts, which serve as interaction spaces for bilingual communities. The Catch Up Club podcast was selected as the research object because it exhibits intense code-mixing that has not been widely examined in previous studies. This study aims to describe and analyze the types of code-mixing and their usage trends within The Catch Up Club podcast on YouTube. A qualitative approach was employed, using content analysis on the speech in The Catch Up Club Episode 13,